Effective Local Leadership to a Successful Council in the State of Terengganu, Malaysia - Aizuddin Md Rami, Faiq Aziz, Fazilah Razali , Abdullah Ibrahim (International Journal of Advanced Science and Technology, 2020)
The development process is targeted to enhance the life quality of communities in rural regions. Comprehensive development that covers economic, social, educational, health, safety and infrastructural development has become the main goal for developing rural communities in Malaysia.  The local leaders, especially the Villages Development and Safety Council (VDSC) play an important role in achieving Government's intention by making sure that such process runs smoothly. This research study was established in 4 rural communities in Malaysia in order to examine the effective role of local heads of community. The base of selection of these communities was their excellency in terms of their records of achievement in competitions and development programmes. Based on the results, it is shown that strategic leader plays a crucial part as the instrument of change and is able to influence rural community development in a positive way. The imperative leadership approach of these community leaders is viewed as capable in bringing adjustment and development amongst social, economic and cultural wellbeing of the community, along with the mentality of communities in rural areas. Hereof, the leadership found in these four communities is perceived to manifest changes into greater leadership which becomes an inspiration towards the rest of community leaders.